PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI DIMEDIASI OLEH PEMBERDAYAAN PSIKOLOGI PADA KARYAWAN PT. PLN (PERSERO) DI WARU SIDOARJO - NUZULUL FATIMAH; RATNA SARI DEWI (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2015)
The purpose of this study was to determine the direct effect of transformational leadership style, mediated by organizational commitment on employee empowerment psychology. This research was conducted by a quantitative approach, Sample in this study were all employees of PT. PLN (Persero) in WaruSidoarjo. Using sampling accidential and simple regression analysis with SPSS 17.0 software. After testing the hypothesis, the obtained t count> t table = 3.571> 1.657 thus concluded that leadership style variable Transfotmasional no significant influence on Organizational Commitment. And to the results of Psychology Empowerment through path analysis with Sobel test calculation at 15.67 with 0:05 significance level that is equal to 1657 it was concluded that the coefficient of 0.18165 significance mediation mediation means no influence psychological empowerment in the style of transformational leadership on organizational commitment. And the results of this study stated that the effect on the Transformational Leadership Organizational Commitment in mediation by Empowerment Psychology.